Digital grooming: discourses of manipulation and cyber-crime - Lorenzo-Dus, Nuria (Oxford studies in sociolinguistics, 2023)
"This book examines digital grooming as a discourse manipulation practice in digital spaces that are situated at, or beyond, the boundaries of law. It identifies and examines in detail the online discourse of adults' luring of children for sexual abuse and exploitation (digital sexual grooming); extreme ideology groups' aligning others to their views (digital ideological grooming); and drug dealers' transactional endeavours in crypto markets (digital commercial grooming). Style and stance analyses of large and varied datasets reveal that digital sexual, ideological and commercial groomers' practices have more in common than not. Three stances-expertise, openness and avidity-scaffold their manipulative work, which relies upon and constructs identity homogenisation. Digital groomers' discourse seeks to construct them and their targets as inhabiting a perfectly aligned ideological, affective and overall identity space. The better aligned they are, the more likely it is that they will see themselves as being dis-aligned from another equally homogenously constructed identities: their opponents'. The findings of this book can inform practitioner-based attempts at countering digital grooming, including development of detection software and prevention-focused training resources"--